Special Delivery - Steel, Danielle (London Corgi Books, 1998)
At fifty-nine, Jack Watson owns one of the most successful boutiques in Beverley Hills, has two grown-up children who are the light of his life, and his choice of Hollywood's most beautiful women. After a failed marriage in the distant past, Jack has become the perfect bachelor. And he loves it.
Originally published: London : Bantam, 1997.
Keywords: California--Los Angeles -- Older Women -- Courtship